Age-related disparities in national maternal mortality trends: A population-based study. - Ryan S Huang; Andrea R Spence; Haim A Abenhaim (PLoS ONE)
Objective An upward trend in maternal age has been observed in the United States (US) over the last twenty years. The study objective was to examine the association of maternal age with maternal mortality in the US and examine temporal trends in mortality by maternal age. Methods A retrospective population-based analysis in the US between 2000-2019 was conducted using records from the Centers for Disease Control and Prevention's "Mortality Multiple Cause" and "Birth Data" files. Annual incidence and period trends in maternal deaths were calculated using the annual maternal deaths over annual live births across age groups. Multivariate logistic regression models were used to estimate the association between maternal age and risk of maternal mortality and calculate temporal changes in risk of mortality over the study period. Results Between 2000-2019, 21,241 deaths were observed in women during pregnancy and childbirth for an average incidence of 26.3 maternal deaths/100,000 births (95% CI 21.8-31.2). Of all deaths, 6,870 (32.3%) were in women ≥35 years, while only 15.1% of live births were attributed to women ≥35 years. Compared with women 25-29 years of age, there was a significantly greater risk of maternal mortality among women 35-39 (OR 1.60, 1.53-1.67), 40-44 (3.78, 3.60-3.99), 45-49 (28.49, 26.49-30.65) and 50-54 (343.50, 319.44-369.37). Risk of mortality increased over time, with the greatest rise in women ≥35 years. Conclusion In the US, maternal mortality increased during the past two decades, especially in women ≥35 years. Given these findings, targeted strategies to reduce the increasing maternal mortality should become a priority.